Informática na educação: importância da utilização das tecnologias digitais da informação e comunicação no ensino fundamental. - DANTAS, Diene Bruna Nunes do Nascimento (2022)
The aim of this article was to understand the importance of using Digital Information and Communication Technologies (DICTs) in Elementary Education. Methodologically, this is an exploratory bibliographical research, with a qualitative approach, whose data source consisted of printed or digital publications in the form of books, articles, monographs, dissertations, theses, etc., in Portuguese, between the years 2016 and 2022 that meet the criteria of the topic addressed. The review allowed conceiving Digital Information and Communication Technologies as the convergent set of technologies, especially computing and telecommunications, that use digital language to produce, store, process and communicate large amounts of information in short periods of time, and that convergence technology favored by the digital language has radically transformed the forms, magnitudes and speeds in the processing and transmission of information. It was also possible to explain the importance of TDICs in education, as the introduction of these technologies in the classroom meant a change in the methodology of 21st century education, in addition to bringing a positive impact on school learning, increasing student motivation and interactivity.